Exploring Female Commodification in Efua T. Sutherland`s The Marriage Of Anansewa - Junior Mensah, Raphael; Biney Evadzi, Charlotte (International Journal of Language and Literary Studies, 2025)
The female body has often been regarded as a commodity across various historical phases, including capitalism and colonialism. In the absence of wealth or personal property, the female body assumes an exchange-value status. Numerous literary texts, such as Woman at Point Zero and From a Crooked Rib, foreground this commodification. Similarly, Efua Sutherland’s The Marriage of Anansewa addresses the issue of female commodification. Drawing on feminist theory, this paper employs a qualitative research design to conduct a literary analysis of how the female body is commodified in The Marriage of Anansewa. The findings reveal that Anansewa is commodified by her father, who exploits her bride price to address his economic challenges, arranging a transactional marriage with four chiefs whose pursuit of her underscores patriarchal dominance. However, the study also shows that she partially resists this commodification through her songs and “staged” death to reclaim the female agency and decides on who to marry. Furthermore, dramatic techniques such as characterization, stage directions, and symbolism, are used to illustrate the commodification and resistance of Anansewa who is seen as an “object of interest.” The study concludes the play is relevant in contemporary discussions on gender, autonomy, and equality in African literature..